SOSIALISASI PEMANFAATAN TIK DALAM MENINGKATKAN AKSES E- ADMINISITRASI DESA KERTAJAYA KECAMATAN PEBAYURAN - Fatah, Abdul; Suryani, Elvira; Maysaroh Chairunnisa, Nurlaila (An-Nizam, 2023)
The purpose of this socialization activity is as a form of application of the third Higher Education Tri Dharma, namely community service. The target in this activity is the village apparatus. The method used in Community Service is carried out with village officials, namely offline socialization. The material presented in this activity is related to the use of ICT in improving E-Administration, especially in Kertajaya Village, Pebayuran District. The purpose of this activity is to meet directly with village officials and the surrounding community to hear what opinions they want to propose to the village government. The potential of village- owned human resources is the main capital for increasing village officials' knowledge of ICT in order to improve E-Administration in the Village Kertajaya especially in a sophisticated era like this where everything is already using electronic technology.